ANALISIS PENGENDALIAN BAHAN BAKU EXCAVA 200 PADA PT. PINDAD MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) UNTUK MENGANTISIPASI TERJADINYA KONDISI STOCKOUT - Elvira Risha Desianty, (2023)
PT. XYZ is a manufacturing company that produces defense and security equipment, as well as products for construction and mining, including Excavators. However, the company faces inventory control issues in the production of Excavators. Three components that frequently experience stockouts are Engine Complete, Wiring Harness, and bolts. Component ordering is based on estimates or the quantity of raw materials from the previous period. The company also lacks safety stock, so if raw material delivery is delayed, production halts. This can lead to product delivery delays, customer dissatisfaction, and decreased customer satisfaction. Therefore, this study aims to analyze the raw material control of Excavators in PT. XYZ using the Material Requirement Planning (MRP) method to anticipate stockouts. The research results indicate that the optimal ordering quantity for Engine Complete is 28 units per month, Wiring Harness is 698 units per period, and Bolt B1 is 468 pcs, Bolt B2 is 34 pcs, Bolt B3 is 359 pcs, Bolt B4 is 398 pcs, and Bolt B5 is 382 pcs. To address stockouts, the company needs to maintain safety stock of 10 units of Engine Complete, 244 units of Wiring Harness, Bolt B1 by 107 pcs, Bolt B2 by 123 pcs, Bolt B3 by 73 pcs, Bolt B4 by 220 pcs, and Bolt B5 by 100 pcs. By implementing the MRP method, PT. XYZ can improve inventory control, avoid stockouts, and enhance customer satisfaction. The inventory cost analysis shows that the use of the MRP method can generate higher revenue potential of approximately Rp364,800,000,000 and save inventory costs per unit of Excavator. This study provides a recommendation for PT. XYZ to implement an effective inventory control system using the MRP method. Thus, operational processes can run smoothly and customer satisfaction can be fulfilled.